Sosialisasi Penggunaan Bahan Bangunan Heritage dan Perkembangannya: Kolaborasi Komunitas Peneliti Heritage Philiphina di Kota Semarang - I Wayan Andhika Widiantara; Eko Nursanty; Wawan Destiawan; Krismawanti Krismawanti (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2022)
Heritage buildings are not only concerned with the shape and design of heritage that has been passed down from one generation to the next. The materials and technologies used are part of the inheritance of objects and intangibles that help strengthen the authenticity in a heritage work. This activity is a collaboration between the heritage community in Semarang City and Manilla City who visited Semarang. This activity aims to understand the authenticity of a heritage architectural work through material and technological elements in Asia through a comparison of similar works in the cities of Semarang and Philippine. The results of this activity are expected to be able to find a picture of authenticity in several examples of traditional architectural works in Asia and provide alternatives for the formation of place identities both in the city of Semarang and Manila.